2011
DOI: 10.1002/tl.442
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and facilitating self‐regulated help seeking

Abstract: Many students are reluctant to seek needed help. In this chapter, we review research on help seeking as a self‐regulated learning strategy and describe a set of interventions designed to promote effective use of help seeking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1
34

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 21 publications
5
64
1
34
Order By: Relevance
“…Similar follow up studies have supported this finding including Karabenick [7] and Karabenick and Dembo [8]. This might suggest that even when high-risk students become more cognizant of their incompetence and lack of knowledge they may still not be likely to access academic support.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar follow up studies have supported this finding including Karabenick [7] and Karabenick and Dembo [8]. This might suggest that even when high-risk students become more cognizant of their incompetence and lack of knowledge they may still not be likely to access academic support.…”
Section: Discussionsupporting
confidence: 64%
“…To high risk students attending SI could imply incompetence and pose a threat to the self-worth of students who are struggling [8]. Paired with the voluntary nature of this academic support its benefits are not likely being as widely realized as they could be.…”
Section: Discussionmentioning
confidence: 99%
“…Help-seeking is situated in selfregulated learning and influenced by the environment (Karabenick & Dembo, 2011). Previous research has demonstrated that many factors may influence student help-seeking behavior, such as the perception of the instructor and the perceived achievement orientation of the class, but has not identified how learner perceptions may be influenced intentionally by the instructor (Karabenick, 2004;Kozanitis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, this study explored how one instructor-controlled environmental factor, the achievement goal orientation of assignments, influenced help-seeking. Research has demonstrated that environments perceived as masteryoriented by the learner positively influence adaptive help-seeking (Karabenick & Dembo, 2011). For instructors and designers, the issue of how to create this mastery-oriented environment has largely been left largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, it could be argued that students who use Learning Advisory services are those who are keen to achieve and are therefore more successful. For example, help seeking has been seen as a valuable component in successful students' approach to their study (Karabenick & Dembo, 2011;Karabenick, 2001). However there is still a lack of published research to validate that learning advisory services taken across a whole year's cohort either in a university or institute of technology and polytechnic (ITP) setting in New Zealand has a positive effect on student retention and success.…”
Section: Introductionmentioning
confidence: 99%